Philosophy Of Science in the Era of Society 5.0: Reflections on the Role of Artificial Intelligence - Faujian Lhaystari Dea; Siti Fatimah (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
This article aims to reflect on the relevance of the philosophy of science in facing the dynamics of the Society 5.0 Era, which is characterized by the dominance of artificial intelligence (AI). This research uses a qualitative method with a descriptive-philosophical approach and library research. Data were collected through a critical review of reliable primary and secondary sources. The research findings indicate that the philosophy of science still plays a crucial role as a reflective foundation for understanding the nature of knowledge, truth, and values ​​amidst technological advances. Artificial intelligence, although capable of expanding analytical capacity and data processing efficiency, is instrumental and cannot replace the role of humans as epistemic subjects with moral awareness and interpretative abilities. In conclusion, the integration of AI in Society 5.0 must always be accompanied by philosophical reflection that emphasizes the relationship between knowledge, values, and ethical responsibility, so as to create a society that is not only technologically intelligent but also based on human values.